Review of the Authorities of the Notary Office and the Legal Consequences for Making Authentic Deeds Against the Law - Mei Elfriana Saragih; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The authority obtained by a notary in making authentic deeds is recognized by law as having perfect evidentiary power. in many cases where notaries are proven to have committed acts against the law resulting in legal consequences in the form of sanctions, these conditions are the background of this research. The purpose of this study is to determine the authority of a notary in society and the legal consequences of making authentic deeds that are against the law. The type of research used is normative legal research. normative legal research, namely research conducted by examining library materials or secondary data. The approach used is a statute approach and a case approach. The type of data in this study is secondary data, namely data obtained from empirical materials. This research is descriptive analysis in nature. The authority of a Notary in UUJN is mentioned in Article 15. This authority includes the authority to make authentic Deeds regarding all actions, agreements, and stipulations required by laws and regulations and/or desired by interested parties to be stated in the Deed authentic. Notaries will receive legal consequences in the form of civil, administrative and even criminal sanctions if proven against the law. The conclusion from this research is that a Notary as a public official in society has his authority regulated by applicable law, and his authority is inseparable from the laws relating to his actions in society. So that notaries as public officials remain bound by positive law in society, both civil and criminal. Notaries will receive legal consequences in the form of civil, administrative and even criminal sanctions if proven against the law